Energy Market Failures Related with Affordability and Investigation of Measures to Overcome them in Lithuania - Markandya, Anil; Štreimikienė, Dalia (Ekonomika, 2003)
In the pricing of energy there is frequently a conflict between the goals of efficiency and those of equity. Efficiency dictates that the prices should be set at the level of long run marginal cost of supply and all consumers for whom this long run marginal cost is the same should pay the same price. Equity, on the other hand demands that prices should somehow be related to affordability; hence the poor should pay less per unit of energy than the rich. This paper evaluates different mechanisms for ensuring that the supply of energy is affordable by poor and vulnerable households in Lithuania. The schemes looked at are (a) no disconnection of households who do not pay their utility bills, (b) price subsidies to all households funded by higher commercial and industrial tariffs, (c) ‘lifeline’ rates with two or three blocks or with ‘floating blocks’, (c) price discounts for certain categories of customers, e.g. pensioners, (d) a ‘burden limit’ so that households are only required to pay a certain percentage of their disposable income for the service, (e) other “earmarked cash transfers” - i.e. cash for the payment of the utility bill, but based on some household income targets. The schemes are evaluated with respect to criteria of: (i) coverage; (ii) targeting; (iii) predictability; (v) welfare costs; (v) administrative cost and (vi) target consumption. The paper concludes that, the use of lifeline rates and other “earmarked cash transfers” based on some household income targets are the most attractive option for handling the energy affordability issue in Lithuania. Th.e latest scheme is used in neighbouring countries, i.e. Latvia, Estonia and Poland. In Lithuania a ‘burden limit’ scheme is being applied. This scheme is not efficient because is poor in coverage and targeting. Only 6-7% of population received this support in 2000 (the poverty level was 16%). The share of expenses spent on energy amounted to 13,6%, for the richest 10% of population and the poorest 10% spent 15,2% for energy services. The middle class spent 17,2% of their expenses on energy. This means that the evaluation of poverty using this criteria is not appropriate.